The effectiveness of nursing psychoeducation toward family burden and quality life on caregiver of people with schizophrenia in the community - Suharsono Suharsono; Noor Faidah; Moh Hanafi (PAGEPress Publications, 2023)
Introduction: The caregivers of people with schizophrenia have problems that include high family, burden and low quality of life at home. Therefore, this study aims to determine the effectiveness of nursing psychoeducation on family, burdens and quality of life in caregivers of schizophrenia patients in the community. Design and Methods: This study used a pre-test and post-test group control design and repeated measurement with a total of 100 respondents. The treatment group was given weekly nursing psychoeducation for seven sessions. Also, the general linear model (GLM) was used to analyze the result. Results: This study showed that before the intervention of nursing psychoeducation, the average family burden was 49,02 and 46.28 in the treatment and control groups, respectively. This decreased to 38.24 and 37.56 in the first and fourth weeks of posttreatment. Meanwhile, the control group was 44.86 in the first week and 45.62 in the fourth. The psychoeducation had an effect on decreasing the family burden with a p value < 0.001. Moreover, this study showed that before the intervention of nursing psychoeducation, the average caregiver quality of life was 75,72 and 74.24 in the treatment. After treatment, it increased to 91.22 in the first week after intervention and 92.54 in the fourth week of post-intervention. Therefore, the intervention effectively improved the caregiver quality of life with p < 0.001 Conclusions: Nursing psychoeducation can effectively reduce family burdens and improve the quality of life for caregivers.